Mobile-to-mobile wireless channels - Zajić, Alenka (Artech House mobile communications series, 2013)
Present-day mobile communications systems can be classified as fixed-to-mobile because they allow mobility on only one end (e.g. the mobile phone to a fixed mobile operator's cell tower). In answer to the consumer demand for better coverage and quality of service, emerging mobile-to-mobile (M-to-M) communications systems allow mobile users or vehicles to directly communicate with each other